Learning Preferences and Academic Outcomes: Insights from Franciscan-Managed Schools - Cutillas, Anesito L.; Lebosada Jr., Juanito O. (Future Science / FSH-PH Publications, 2024)
This study examines the relationship between learning preferences and academic performance among third-year high school students in two Franciscan-managed schools in Negros Oriental, Philippines. Using the Felder-Silverman Learning Style Model and a descriptive research design, the profiles and preferences of 120 students were analyzed across four dimensions. Pearson’s correlation revealed a significant relationship between gender and academic performance, with females outperforming males, while family size and income showed no significant impact. The sensing/intuitive learning style exhibited a weak but positive relationship with academic outcomes, highlighting the need for differentiated instructional strategies. The findings advocate for gender-sensitive and adaptive teaching approaches to enhance student engagement and holistic development in Franciscan-managed schools.